Implementasi Model Experiential Learning untuk Meningkatkan Kualitas Pembelajaran Biologi Siswa Kelas XI IPA 1 SMA Negeri 2 Surakarta Tahun Pelajaran 2013/2014 - Elisa Dewi Yuliarti; Sajidan Sajidan; Marjono Marjono (Universitas Sebelas Maret, 2014)
The purposes of this research are to increase quality of biology learning considered by utility of facilities in the classroom, classroom climate, and student motivation of achievement in class XI IPA 1 at State Senior High School 2 Surakarta in academic year 2013/2014. This research was a classroom action research which performed in two cycles. Each cycle consisted of 4 phases, that is planning, action, observation, and reflection. Subject of research is students of XI IPA 1 at State Senior High School 2 Surakarta. Data of research was obtained by test and non test technique. Data validation was used triangulation of methods and triangulation of observers. The obtained data were analyzed using descriptive technique. The results of this research showed the average percentage for classroom climate pre cycle (62,59 %), cycle I (75,86 %), and cycle II (82,92 %); student motivation of achievement pre cycle (63,22 %), cycle I (74,88 %) and cycle II (78,62 %); and utility of learning facilities in the classroom have been optimally, that are usage of microscope and other learning media included LCD, pictures, and video as a media to support learning activities. The results showed that the average percentage quality of biology learning aspect such as pre cycle (62,90 %), cycle I (75,37 %), and cycle II (80,77 %). The level increase of quality aspect of biology learning from pre cycle to cycle II is 17,87 %. The conclusion of this research is that the implementation of experiential learning model can improve quality of biology learning considered by utility of facilities in the classroom, classroom climate, and student motivation of achievement in class XI IPA 1 State Senior High School 2 Surakarta in academic year 2013/2014. Key Words: Experiential learning, Quality of biology learning